Role of AtCPK5 and AtCPK6 in the regulation of the plant immune response triggered by rhamnolipids in Arabidopsis - Juliette Stanek; Olivier Fernandez; Marie Boudsocq; Dina Aggad; Sandra Villaume; Laetitia Parent; Sandrine Dhondt-Cordelier; Jérôme Crouzet; Stéphan Dorey; Sylvain Cordelier (PLoS ONE, 2026)
Rhamnolipids (RLs) are bacterial glycolipids with potential applications in the biocontrol of plant pathogens. Although RLs are known to activate plant immune responses, the underlying signaling mechanisms remain poorly understood. Calcium-dependent protein kinases (CPKs) are a large family of kinases involved in various functions in plants including signaling of the plant immunity. Here, we investigated the contribution of At CPK5 and At CPK6 to RL-triggered immunity in Arabidopsis. RL treatment induced the expression of both AtCPK5 and AtCPK6 genes in Arabidopsis leaves. Functional analyses revealed that RL-induced responses, including reactive oxygen species production and the expression of defense-related genes ( AtWRKY46 , AtFRK1 and AtPR1 ), were enhanced in cpk5/6 mutants compared to wild-type plants. The cpk5 mutant exhibited intermediate responses, whereas cpk6 alone had little effect, except on AtFRK1 expression, indicating a predominant role for At CPK5 in regulating RL-triggered signaling. However, cpk5/6 mutations did not affect RL-induced electrolyte leakage or RL-mediated resistance to Pseudomonas syringae pv. tomato DC3000. Together, these results suggest that At CPK5 and At CPK6 negatively modulate RL-triggered immune signaling, while additional components contribute to the regulation of downstream defense responses.